A Subtitling Analysis Of Interrogative Sentence In Monte Carlo Movie - Astuti, Endah Dwi; , Drs. Sigit Haryanto, M.Hum; , Siti Fatimah, S. Pd, M. Hum (2013)
This research studies about a subtitling analysis of interrogative sentence in Monte Carlo movie. The objectives of the study are to explain the types of interrogative sentences and to explain the equivalent translation of interrogative sentences in its subtitle. This research applies descriptive qualitative research. By applying this method, the researcher uses the subtitle of Monte Carlo movie as the data source, while the data of the research are interrogative sentence. As the comparison, there are also data taken from manuscript in English and Indonesian. The method of collecting data is document and interviewing the viewers of the movie to get their opinion of the movie. The technique of analysis applied in this study is descriptive analysis. The result of the research shows that there are 150 data of interrogative sentence. From 150 data of interrogative sentence, the researcher finds types of interrogative sentence: 1) yes-no questions, 2) tag questions, and 3) interrogative word questions. In subtitling analysis, the researcher finds 42 or 28 % data belongs to yes-no questions, 3 or 2% data belong to tag questions, and finally there are 105 or 70% data belongs to interrogative-word questions. From 150 data, the researcher also finds there are 138 or 92% equivalent subtitling and 12 or 8% non-equivalent subtitling.